The paradox of violence and spirituality as seen in Ali : a life 9 2017 ) and kitab galenganing jagad ( 1928 ) ( comparative analysis ) - Bangkit Tri Utomo (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2022)
wt,1/ yna, c.1